Differentiation of Cervical Spine Osteoradionecrosis and Bone Metastasis After Radiotherapy Detected by Bone Scan in Patients With Nasopharyngeal Carcinoma: Role of Magnetic Resonance Imaging - Zhong, Xi; Li, Li; Lu, Bingui; Zhang, Hainan; Huang, Lu; Lin, Xinjia; Li, Jiansheng; Zhang, Jian (Frontiers in Oncology, 2020)
Background: Osteoradionecrosis (ORN) of the cervical spine is a serious complication after radiotherapy (RT), which may show increased radiotracer uptake on a bone scan (BS) and be mistaken as metastasis. We aimed to assess the value of magnetic resonance imaging (MRI) in the differentiation of cervical spine ORN from bone metastasis after RT detected by BS in nasopharyngeal carcinoma (NPC). Methods: In this retrospective study, 35 NPC patients who had undergone RT were enrolled, of whom 21 patients showed cervical spine ORN and 14 showed bone metastasis. New areas of increased radiotracer uptake in the cervical spine on a BS were noted in all patients, following which the patients underwent neck MRI for further assessment. Two radiologists independently reviewed two sets of images including a BS set and an MRI set (MRI with BS) and reached a consensus. The diagnostic sensitivity, specificity, and accuracy for ORN detection were calculated, and interobserver agreement was evaluated using the kappa test. Results: A total of 75 cervical spine lesions were identified (44, ORN; 31 metastases). The BS set analysis showed that the diagnostic sensitivity, specificity, and accuracy were only 38.6%, 48.3%, and 42.7%, respectively, for differentiation of cervical spine ORN from bone metastasis. On the other hand, the MRI set analysis showed that the diagnostic sensitivity, specificity, and accuracy increased to 86.4%, 90.3%, and 88.0%, respectively. The interobserver agreement for the MRI set was determined to be very good (κ = 0.92). Conclusion: MRI is a reliable technique for the further discrimination of emerging cervical spine lesions after RT detected by BS. Furthermore, it could be a better differential diagnosis technique for distinguishing ORN from metastasis and may help avoid a wrong assignment of the patient to a metastatic stage with indication for treatment with supplemental toxicity and a subsequent palliative strategy.